Poverty Alleviation in the Hope Family Program in Makassar City - Parawangi, Anwar; Wahid, Nur (Universitas Muhammadiyah Malang, 2023)
The Family Hope Program (PKH) is one of the important instruments in reducing the high poverty rate in Makassar City. This article aims to see how the implementation of the PKH program. This research is social in nature in the realm of public policy. The writing method used is qualitative with a normative descriptive approach. This research shows that this program generally contributes to reducing poverty in Makassar City. However, there is also a negative response to the lack of public understanding of PKH, so in the process of distributing aid, it is still considered discriminatory. The performance of the implementation of the family hope program is strongly influenced by the characteristics of the participants, namely supporting, or rejecting. In other words, the successful implementation of the PKH program is largely determined by support and a conducive environment.